Ansel Adams in the national parks : photographs from America's wild places - Stillman, Andrea Gray; Adams, Ansel, 1902-1984 (Little, Brown, 2010)
For many Americans, the names Yosemite, the High Sierra, and the Grand Canyon conjure up first and foremost an Ansel Adams photograph. A lifelong environmentalist, Adams was one of the most ardent champions of our national parks and wilderness systems, and through his magnificent photographs, letter-writing campaigns, and Sierra Club activities, he arguably did more than any individual since John Muir to raise our awareness and appreciation of America's wild places. He visited more than forty national parks in his lifetime, lugging an 8xio-inch view camera, tripod, and photographic gear through dense old-growth forest and over precarious mountain passes, often with a burro as traveling companion and baggage handler. His customized wood-paneled station wagon, nicknamed Helios, took him across the land and boasted a photographic platform on its roof, a mobile stage from which he could gain the best possible vantage points for image making. With more than 225 photographs, many rarely seen and 50 never before published, Ansel Adams in the National Parks is the most comprehensive book of Adams' photographs of our national parks and wilderness areas. Edited by Andrea G. Stillman, who worked for Adams in the 1970s, it features original essays by critic Richard B. Woodward and commentary by Stillman on the making of numerous photographs, enlivened by quotations from Adams. Essays by Wallace Stegner, William A. Turnage of The Ansel Adams Trust, and Adams himself capture the essence of Ansel Adams as both gifted photographer and passionate environmentalist.